Old ways for new days : Indigenous survival and agency in climate changed times - Nursey-Bray, Melissa; Palmer, Robert; Chischilly, Ann Marie; Rist, Phil; Yin, Lun (SpringerBriefs in climate studies., 2022)
This Open Access book provides a critical reflection into how Indigenous cultures are attempting to adapt to climate change. Through detailed first-hand accounts, the book describes the unique challenges facing Indigenous peoples in the context of climate change adaptation, governance, communication strategies, and institutional pressures. The book shows how current climate change terminologies and communication strategies often perpetuate the marginalisation of Indigenous peoples and suggests that new approaches that prioritise Indigenous voices, agency and survival are required. The book first introduces readers to Indigenous peoples and their struggles related to climate change, describing the impacts of climate change on their everyday lives and the adaptation strategies currently undertaken to address them. These strategies are then detailed through case studies which focus on how Indigenous knowledge and practices have been used to respond to and cope with climate change in a variety of environments, including urban settings. The book discusses specific governance challenges facing Indigenous peoples, and presents new methods for engagement that will bridge existing communication gaps to ensure Indigenous peoples are central to the implementation of climate change adaptation measures. This book is intended for an audience of Indigenous peoples, adaptation practitioners, academics, students, policy makers and government workers.